2016
DOI: 10.1142/s1793545816420013
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green loaded graphene oxide for high-efficient photoacoustic tumor therapy

Abstract: Photoacoustic therapy, using the photoacoustic e®ect of agents for selectively killing tumor cells, has shown promising for treating tumor. Utilization of high optical absorption probes can help to e®ectively improve the photoacoustic therapy e±ciency. Herein, we report a novel highabsorption photoacoustic probe that is composed of indocyanine green (ICG) and graphene oxide (GO), entitled GO-ICG, for photoacoustic therapy. The attached ICG with narrow absorption spectral pro¯le has strong optical absorption in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…An indocyanine green modified GO could convert the absorbed light energy with high efficiency to acoustic wave under pulsed laser irradiation. The presented results confirm that the strong laser-induced wave from integrin-targeted indocyanine green-loaded GO could effectively induce U87-MG cell apoptosis thus showed high efficiency in killing tumor cells [125].…”
Section: Targeting Moietiessupporting
confidence: 65%
“…An indocyanine green modified GO could convert the absorbed light energy with high efficiency to acoustic wave under pulsed laser irradiation. The presented results confirm that the strong laser-induced wave from integrin-targeted indocyanine green-loaded GO could effectively induce U87-MG cell apoptosis thus showed high efficiency in killing tumor cells [125].…”
Section: Targeting Moietiessupporting
confidence: 65%
“…Since loading efficacy of ICG in modified nano-graphene oxide is markedly higher in comparison with those of PLGA and other ICG encapsulating nanoparticles such as liposome, which is reported to have a low stability and loading capacity below 10% (19,26). Another advantage of nGO is not using toxic metals in its synthesis, which makes it mass production easy and cost-effective in addition to its biocompatibility (20). It is shown that incorporating ICG into nGO increases its photo and physicochemical stability through rich π-π stacking interactions and improves its biocompatibility (19).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it should have optical window (600 -900 nm) for sufficient tissue penetration (18). A good candidate is indocyanine green (ICG) as an amphiphilic dye, also known as CardioGreen®, as the only food and drug administration (FDA)-approved PS (19), with the unique peak absorbance at 780 nm (20,21). Most PSs such as ICG, have limitations such as little photostability and concentration-related aggregation (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Yan et al fabricated ICG-loaded GO for the application of PA-based tumor therapy [ 74 ]. The absorption spectrum of GO–ICG showed 10-fold enhanced absorbance compared to pristine GO at its peak region (780 nm) because of ICG’s FL quenching by the resonance energy transfer of GO.…”
Section: Graphene-based Photoacoustic Imagingmentioning
confidence: 99%